Do current quality measures truly reflect the quality of dialysis?. Issue 4 (26th February 2018) - Gupta, Nupur; Wish, Jay B.
Abstract: The US End Stage Renal Disease (ESRD) Program, which came into existence in 1973, was initially envisioned to provide needed financial coverage for about 50 000 patients through Medicare. Over the past 45 years the evolution of the ESRD program has been quite different, and it now serves over one half million dialysis and transplant patients. The Medicare Improvements for Patients and Providers Act (MIPPA) of 2008 Section 153(c) requires the Centers for Medicare and Medicaid Services (CMS) to develop and implement quality measures for dialysis patients as part of the ESRD Quality Incentive Program (QIP) beginning in payment year (PY) 2012. The annual ESRD Prospective Payment System (PPS) rulemaking process allows CMS to create ESRD QIP rules that specify the measures, scoring methods, and payment reduction ranges applicable to the respective PY. CMS assesses each facility's performance and calculates a score for each measure, according to the method detailed for that PY. Scores for each measure are combined to create the Total Performance Score (TPS) for each facility. If a facility's TPS does not meet or exceed the performance standards established during the earlier comparison period, the facility will incur a payment reduction of up to 2% for the entire PY. The QIP program has evolved over the several years since its inception. There have been deletions and additions of various measures. CMS uses additional measures in its Dialysis Facility Compare (DFC) website which is available to the public and forms the basis of the 5‐star rating system for dialysis facilities. The evidence underlying inclusion many of these measures in the QIP and DFC remains an area of debate. In this review, we discuss the evolution of these measures and their appropriateness. We recommend that some of the current QIP and DFC measures should not be used for public reporting and/or payment as unintended consequences may occur. Nonetheless, all the current QIP and DFC measures and others are suitable for internal quality review.